Drill rod and preparation method thereof
By forming carburizing-silicon-nitrogen layer and nanotitanium nitride and nanotitanium carbide composite coatings on the surface of the drill pipe, the problem of poor corrosion and wear resistance of drill pipes is solved, and high hardness and low Wear and high corrosion resistance extend the service life of the drill rod.
Patent Information
- Application Number
- CN202310759578.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
Existing drill rods have poor performance in corrosion and wear resistance, resulting in shorter service life.
Using the composite structure of carburizing-silicon-nitrogen layer, nanotitanium nitride layer and nanotitanium carbide layer, high hardness and strong bond resistance are formed on the surface of the drill pipe body through plasma carburizing-silicon-nitrogen process and chemical deposition technology. Corrosion coating.
Significantly improve the surface hardness of the drill rod, reduce wear rate, enhance wear resistance and corrosion resistance, and extend service life.
Smart Images

Figure CN119194341A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of drill rod manufacturing, and in particular to a drill rod and a preparation method thereof. Background Art
[0002] Drill pipes are commonly used downhole tools for oil and gas field exploitation. They face an increasingly harsh corrosive environment. How to protect drill pipes from corrosion has become an important issue in improving the service life of oil and gas drill pipes. At present, there are two methods for improving the service life of drill pipes. One is to use corrosion-resistant alloys, such as titanium alloys. Compared with carbon steel drill pipes, titanium alloy drill pipes have better corrosion resistance and longer service life. However, due to the low hardness and poor wear resistance of titanium alloys, titanium alloy drill pipes still have serious wear and corrosion problems. Another method is to use electroplating or chemical plating methods to coat the surface of the carbon steel drill pipe with a metal coating to achieve wear and corrosion resistance. However, the coatings prepared by existing electroplating and chemical plating processes have the disadvantages of low hardness, weak bonding strength, and poor wear resistance, which can easily cause the protective coating to fall off and cause wear and corrosion of the drill pipe, thereby shortening the service life of the carbon steel drill pipe.
[0003] In view of the above problems, it is necessary to provide a drill pipe having good corrosion resistance and wear resistance and a preparation method thereof. Summary of the invention
[0004] The main purpose of the present invention is to provide a drill rod and a preparation method thereof, so as to solve the problem that the existing drill rod has poor performance in corrosion resistance and wear resistance.
[0005] In order to achieve the above-mentioned purpose, the present invention provides a drill pipe on the one hand, which includes a drill pipe body, a carburizing-silicon-nitrogen layer arranged on the surface of the drill pipe body in sequence, a corrosion-resistant layer, and a female joint and a male joint connected to the drill pipe body, wherein the corrosion-resistant layer includes: a nano-titanium nitride layer, the nano-titanium nitride is arranged on the surface of the carburizing-silicon-nitrogen layer away from the drill pipe body; and a nano-titanium carbide layer, the nano-titanium carbide layer is arranged on the surface of the nano-titanium carbide layer away from the carburizing-silicon-nitrogen layer.
[0006] Furthermore, the thickness of the carburized-silicon-nitrogen layer is 100-200 μm, and the total thickness of the nano-titanium nitride layer and the nano-titanium carbide layer is 4-10 μm.
[0007] Furthermore, the thickness of the nano titanium nitride layer is 3 to 6 μm, and the thickness of the nano titanium carbide layer is 1 to 4 μm.
[0008] Furthermore, the particle size of the nano titanium nitride particles in the nano titanium nitride layer is 100-400 nm.
[0009] Furthermore, the nano titanium nitride layer includes multiple layers, and along the direction from the carburized-silicon-nitrogen layer to the nano titanium carbide, the particle sizes of the nano titanium nitride layer are arranged in order from large to small.
[0010] Furthermore, the nano-titanium carbide in the nano-titanium carbide layer is in the form of block-shaped particles, and the particle size of the block-shaped nano-titanium carbide particles is 100-200 nm.
[0011] Furthermore, the ratio of the particle size of the nano-titanium nitride particles in the nano-titanium nitride layer to the particle size of the nano-titanium carbide particles in the nano-titanium carbide layer is 1:2 to 4:1.
[0012] The second aspect of the present application also provides a method for preparing the above-mentioned drill pipe, characterized in that the method for preparing the drill pipe comprises: performing carburizing-silicon-nitrogen treatment on the inner and outer surfaces of the drill pipe body to form a carburizing-silicon-nitrogen layer; performing a first chemical deposition on the surface of the carburizing-silicon-nitrogen layer to form a nano titanium nitride layer; and performing a second chemical deposition on the surface of the nano titanium carbide layer to form a nano titanium carbide layer to obtain the drill pipe.
[0013] Furthermore, the temperature of the carburizing-silicon-nitrogen treatment is 400-550° C., and the carburizing-silicon-nitrogen treatment time is 2-6 hours.
[0014] Furthermore, the temperature of the first chemical deposition is 450-650° C., and the processing time is 1-5 hours.
[0015] Furthermore, the temperature of the second chemical deposition is 450-650° C., and the processing time is 1-5 hours.
[0016] By applying the technical solution of the present invention, the carburized-silicon-nitrogen layer arranged on the inner and outer surfaces of the drill pipe body can improve the hardness and strength of the drill pipe body, and at the same time form a carbon-silicon-nitrogen transition layer to alleviate the thermal expansion coefficient mismatch between the nano-titanium nitride layer and the drill pipe body, and reduce the interface stress, thereby enhancing the film-substrate bonding strength. Since the titanium nitride in the nano-titanium nitride layer is a nano-scale particle, it can form a strong interface bond with the carburized-silicon-nitrogen layer on the surface of the drill pipe body compared to the ordinary titanium nitride layer, thereby improving its bonding force with the carburized-silicon-nitrogen layer and the wear resistance of the nano-titanium nitride layer. Compared with the ordinary titanium carbide layer, the nano-titanium carbide layer has a better bonding ability with the nano-titanium nitride layer, and the nano-titanium carbide particles have a higher hardness, which can further enhance the overall hardness, wear resistance and corrosion resistance of the coating. On this basis, the composite structure layer formed by the above-mentioned carburized-silicon-nitrogen layer, nano-titanium nitride layer and nano-titanium carbide layer has excellent properties such as high hardness, strong bonding, low wear and high corrosion resistance, which can significantly improve the surface hardness of the drill pipe and reduce the wear rate of the drill pipe, thereby improving the wear resistance and corrosion resistance of the drill pipe. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic diagram of a corrosion-resistant drill pipe structure provided for a preferred embodiment of the present invention.
[0019] Figure 2 A schematic diagram of the structure of a carburized-silicon-nitrogen layer and a corrosion-resistant coating on the surface of a corrosion-resistant drill pipe body provided in a preferred embodiment of the present invention.
[0020] Figure 3 This is a morphology test diagram of the titanium carbide layer in the corrosion-resistant layer of the drill pipe prepared in Example 1 of the present application.
[0021] Figure 4 This is a test diagram of the friction performance of the corrosion-resistant layer in the drill pipe prepared in Example 1 of the present application.
[0022] Figure 5 This is a test chart of the wear performance of the corrosion-resistant layer in the drill pipe prepared in Example 1 of the present application.
[0023] The above drawings include the following reference numerals:
[0024] 10. Drill pipe body; 20. Carburized-silicon-nitrogen layer;
[0025] 30. Corrosion-resistant layer; 31. Nano titanium nitride layer; 32. Nano titanium carbide layer;
[0026] 40, female connector; 50, male connector. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0028] As described in the background technology, the existing drill pipe has poor performance in corrosion resistance and wear resistance. In order to solve the above technical problems, the present application provides a drill pipe, including a drill pipe body 10, a carburized-silicon-nitrogen layer 20 sequentially arranged on the inner and outer surfaces of the drill pipe body 10, a corrosion-resistant layer 30, and a female connector 40 and a male connector 50 connected to the drill pipe body 10, wherein the corrosion-resistant layer 30 includes a nano-titanium nitride layer 31 and a nano-titanium carbide layer 32, the nano-titanium nitride is arranged on the surface of the carburized-silicon-nitrogen layer 20 away from the drill pipe body 10, and the nano-titanium carbide layer 32 is arranged on the surface of the nano-titanium carbide layer 32 away from the carburized-silicon-nitrogen layer 20.
[0029] The carburized-silicon-nitrogen layer 20 disposed on the inner and outer surfaces of the drill pipe body 10 can improve the hardness and strength of the drill pipe body 10, and at the same time form a carbon-silicon-nitrogen transition layer to alleviate the thermal expansion coefficient mismatch between the nano-titanium nitride layer and the drill pipe body, and reduce the interface stress, thereby enhancing the film-substrate bonding strength. Since the titanium nitride in the nano-titanium nitride layer 31 is a nano-scale particle, it can form a strong interface bond with the carburized-silicon-nitrogen layer 20 on the surface of the drill pipe body 10 compared to the ordinary titanium nitride layer, thereby improving its bonding force with the carburized-silicon-nitrogen layer 20 and the wear resistance of the nano-titanium nitride layer 31. Compared with the ordinary titanium carbide layer, the nano-titanium carbide layer 32 has a better bonding ability with the nano-titanium nitride layer 31, and the nano-titanium carbide particles have a higher hardness, which can further enhance the hardness, wear resistance and corrosion resistance of the coating. On this basis, the composite structure layer formed by the above-mentioned carburized-silicon-nitrogen layer 20, nano-titanium nitride layer 31 and nano-titanium carbide layer 32 has excellent properties such as high hardness, strong bonding, low wear and high corrosion resistance, which can significantly improve the surface hardness of the drill pipe and reduce the wear rate of the drill pipe, thereby improving the wear resistance and corrosion resistance of the drill pipe.
[0030] It should be noted that the carburized-silicon-nitrogen layer 20 and the corrosion-resistant layer 30 may be provided only on the inner surface of the drill pipe body 10, or only on the outer surface thereof, or on both the inner and outer surfaces.
[0031] The main function of the carburized-silicon-nitrogen layer 20 is to enhance the surface hardness of the drill pipe body 10 and to match the thermal expansion coefficient of the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32 to reduce the interface stress and enhance the bonding strength between the drill pipe body 10 and the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32. Preferably, the thickness of the carburized-silicon-nitrogen layer 20 is 100 to 200 μm.
[0032] Under the condition that the carburized-silicon-nitrogen layer 20 maintains the above thickness, preferably, the sum of the thicknesses of the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32 is 4 to 10 μm. The composite structure layer formed by the above-mentioned carburized-silicon-nitrogen layer 20, the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32 can significantly improve the wear resistance and corrosion resistance of the drill pipe. More preferably, the thickness of the nano-titanium nitride layer 31 is 3 to 6 μm, and the thickness of the nano-titanium carbide layer 32 is 1 to 4 μm. The structures of the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32 include but are not limited to the above ranges, and limiting them within the above ranges is conducive to further improving the wear resistance and corrosion resistance of the drill pipe.
[0033] The titanium nitride particles in the nano-titanium nitride layer 31 are nano-sized, which makes them have a high bonding force with the carburized-silicon-nitrogen layer 20 and the titanium carbide layer. Preferably, the particle size of the nano-titanium nitride particles in the nano-titanium nitride layer 31 is 100-400nm.
[0034] In a preferred embodiment, the particle size of the nano-titanium carbide particles in the nano-titanium carbide layer 32 is 100 to 200 nm. Limiting the particle size of the nano-titanium carbide particles in the nano-titanium carbide layer 32 to the above range can further improve the compactness of the nano-titanium carbide layer 32 and the bonding force with the nano-titanium nitride layer 31, thereby further improving its wear resistance and corrosion resistance. More preferably, the ratio of the particle size of the titanium nitride particles in the nano-titanium nitride layer 31 to the particle size of the nano-titanium carbide particles in the nano-titanium carbide layer 32 is 1:2 to 4:1.
[0035] Preferably, the friction coefficient of the drill rod surface is 0.1-0.3; the volume wear rate is ≤3.5×10 -6 mm 3 / N·m.
[0036] Preferably, the female connector 40, the male connector 50 and the drill pipe body 10 are all made of carbon steel, and the female connector 40, the male connector 50 and the drill pipe body 10 are all connected by threads, so that a complete corrosion-resistant drill pipe is finally obtained.
[0037] The second aspect of the present application also provides a method for preparing the above-mentioned drill rod, which comprises: performing carburizing-silicon-nitrogen treatment on the inner and outer surfaces of the drill rod body 10 to form a carburizing-silicon-nitrogen layer 20; performing a first chemical deposition on the surface of the carburizing-silicon-nitrogen layer 20 to form a nano-titanium nitride layer 31; and performing a second chemical deposition on the surface of the nano-titanium carbide layer 32 to form a nano-titanium carbide layer 32 to obtain a drill rod.
[0038] The formation of a carburized-silicon-nitrogen layer 20 on the inner and outer surfaces of the drill pipe body 10 by a plasma carburizing-silicon-nitrogen process can improve the hardness and strength of the drill pipe body 10. A nano-titanium nitride layer 31 and a nano-titanium carbide layer 32 are sequentially formed on the surface of the carburized-silicon-nitrogen layer 20 by a first chemical deposition and a second chemical deposition process. Finally, a drill pipe having a composite structure layer formed by a carburized-silicon-nitrogen layer 20, a nano-titanium nitride layer 31 and a nano-titanium carbide layer 32 is obtained. Compared with the existing drill pipe, the drill pipe obtained by the above method has the properties of high surface hardness, low wear rate of the drill pipe, and corrosion resistance. At the same time, the above method is simple, efficient, and industrially popularized.
[0039] In a preferred embodiment, the temperature of the carburizing-silicon-nitrogen treatment is 400-550°C, and the carburizing-silicon-nitrogen treatment time is 2-6 hours. The temperature and time of the carburizing-silicon-nitrogen treatment include but are not limited to the above ranges, and limiting them within the above ranges is conducive to further increasing the carburizing-silicon-nitrogen depth, thereby further improving the hardness and strength of the drill pipe.
[0040] In a preferred embodiment, the temperature of the first chemical deposition is 450-650°C, and the processing time is 1-5 hours; the temperature of the second chemical deposition is 450-650°C, and the processing time is 1-5 hours. The temperature and processing time of the first chemical deposition and the second chemical deposition include but are not limited to the above ranges, and limiting them within the above ranges is conducive to further improving the bonding between the nano-titanium nitride layer 31 and the nano-titanium carbide layer 32 and the lithium, thereby further improving the comprehensive performance of the drill pipe, such as wear resistance and corrosion resistance.
[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0042] Example 1
[0043] A corrosion-resistant drill pipe includes a drill pipe body 10 made of carbon steel. A carburized-silicon-nitrogen layer 20 and a corrosion-resistant coating are present on the inner and outer surfaces of the drill pipe body 10. The left end of the drill pipe body 10 is connected to a female joint 40 through a thread, and the right end is connected to a male joint 50 through a thread. The female joint 40 is an internally threaded joint, and the male joint 50 is an externally threaded joint. Both the female joint 40 and the male joint 50 are made of carbon steel.
[0044] The inner and outer surfaces of the drill pipe body 10 are sequentially provided with a carburizing-silicon-nitrogen layer 20, a nano-titanium nitride layer and a nano-titanium carbide layer 32. The carburizing-silicon-nitrogen temperature of the carburizing-silicon-nitrogen layer 20 is 480°C, the carburizing-silicon-nitrogen time is 5 hours, and the thickness of the carburizing-silicon-nitrogen layer 20 is 180 μm. On the surface of the carburized-silicon-nitrogen layer 20, a nano titanium nitride layer 31 is first prepared by low-temperature chemical vapor deposition; the deposition temperature is 630°C, the deposition time is 4.5h, and the titanium nitride grain size is 300nm, and the titanium nitride layer thickness is 6μm; then a nano titanium carbide layer 32 is prepared on the surface of the nano titanium nitride layer 31 by low-temperature chemical vapor deposition, the deposition temperature is 620°C, the deposition time is 3h, and the titanium carbide grain size is 130nm, and the titanium carbide layer thickness is 4μm; a double-layer structure of the nano titanium nitride layer 31 and the nano titanium carbide layer 32 is obtained, and the corrosion-resistant layer 30 is composed of the double-layer structure. Finally, the female connector 40 and the male connector 50 are respectively connected to the drill pipe body 10 by threads, and finally a complete corrosion-resistant drill pipe is obtained.
[0045] Results
[0046] Figure 3 This is a morphology test diagram of the titanium carbide layer in the corrosion-resistant layer of the drill pipe prepared in Example 1. Figure 3 It can be seen that the grain size of the nano titanium carbide layer 32 in the corrosion-resistant coating on the surface of the corrosion-resistant drill pipe body 10 obtained in Example 1 is nanometer size, the grain size is 80-150nm, the grains are tightly combined, and the coating density is high.
[0047] Figure 4 This is a test diagram of the friction performance of the corrosion-resistant layer in the drill pipe prepared in Example 1. Figure 4 It can be seen that the average friction coefficient of the corrosion-resistant coating on the surface of the corrosion-resistant drill pipe body 10 obtained in Example 1 is 0.13.
[0048] Figure 5 This is a test diagram of the wear performance of the corrosion-resistant layer in the drill pipe prepared in Example 1. Figure 5 It can be seen that the volume wear rate of the corrosion-resistant coating on the surface of the corrosion-resistant drill pipe body 10 obtained in Example 1 is 2.6×10 -6 mm 3 / N·m.
[0049] According to measurement, the elements of the corrosion-resistant layer on the surface of the drill pipe body 10 obtained in Example 1 are titanium and carbon, the weight percentage of carbon is 53.06%, and the weight percentage of titanium is 46.94% (as shown in Table 1).
[0050] Table 1
[0051] element Weight content % C 53.06 Ti 46.94 total 100.00
[0052] Example 2
[0053] The difference from Example 1 is that when forming the carburizing-silicon-nitrogen layer 20, the temperature of the carburizing-silicon-nitrogen process is 400°C, the carburizing-silicon-nitrogen time is 6 hours, and the thickness is 200 μm.
[0054] The corrosion-resistant layer 30 is prepared on the surface of the carburized-silicon-nitrogen layer 20 by plasma enhanced chemical vapor deposition, wherein the thickness of the corrosion-resistant layer is 8 μm, wherein the thickness of the nano titanium nitride layer 31 is 6 μm, and the thickness of the nano titanium carbide layer 32 is 2 μm. The deposition temperature of the nano titanium nitride layer is 520°C, the deposition time is 3 hours, the obtained titanium nitride grain size is 100 nm, and the titanium nitride layer thickness is 2 μm; the deposition temperature of the nano titanium carbide layer is 500°C, the deposition time is 2 hours, the obtained titanium carbide grain size is 100 nm, and the titanium carbide layer thickness is 1.5 μm.
[0055] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.26; the volume wear rate is 3.4×10 -7 cm 3 / N·m.
[0056] Example 3
[0057] The difference from Example 1 is that when forming the carburizing-silicon-nitrogen layer 20, the temperature of the carburizing-silicon-nitrogen process is 500°C, the carburizing-silicon-nitrogen time is 2 hours, and the thickness is 100 μm.
[0058] The corrosion-resistant layer 30 is prepared on the surface of the carburized-silicon-nitrogen layer 20 by plasma enhanced chemical vapor deposition, wherein the thickness of the corrosion-resistant layer is 5 μm, wherein the thickness of the nano titanium nitride layer 31 is 3 μm, and the thickness of the nano titanium carbide layer 32 is 2 μm. The deposition temperature of the nano titanium nitride layer is 550°C, the deposition time is 3 hours, the obtained titanium nitride grain size is 200 nm, and the titanium nitride layer thickness is 3 μm; the deposition temperature of the nano titanium carbide layer is 520°C, the deposition time is 3 hours, the obtained titanium carbide grain size is 170 nm, and the titanium carbide layer thickness is 2.0 μm.
[0059] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.23; the volume wear rate is 3.2×10 -7 cm 3 / N·m.
[0060] Example 4
[0061] The difference from Example 1 is that when forming the carburizing-silicon-nitrogen layer 20, the temperature of the carburizing-silicon-nitrogen process is 550°C, the carburizing-silicon-nitrogen time is 3 hours, and the thickness is 150 μm.
[0062] The corrosion-resistant layer 30 is prepared on the surface of the carburized-silicon-nitrogen layer 20 by plasma enhanced chemical vapor deposition, wherein the thickness of the corrosion-resistant layer is 9 μm, wherein the thickness of the nano titanium nitride layer 31 is 5 μm, and the thickness of the nano titanium carbide layer 32 is 4 μm. The deposition temperature of the nano titanium nitride layer is 450°C, the deposition time is 3 hours, the obtained titanium nitride grain size is 400 nm, and the titanium nitride layer thickness is 4 μm; the deposition temperature of the nano titanium carbide layer is 450°C, the deposition time is 3 hours, the obtained titanium carbide grain size is 120 nm, and the titanium carbide layer thickness is 2.5 μm.
[0063] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.26; the volume wear rate is 3.4×10 -7 cm 3 / N·m.
[0064] Example 5
[0065] The difference from Example 1 is that when forming the carburizing-silicon-nitrogen layer 20, the temperature of the carburizing-silicon-nitrogen process is 550°C, the carburizing-silicon-nitrogen time is 4 hours, and the thickness is 200 μm.
[0066] The corrosion-resistant layer 30 is prepared on the surface of the carburized-silicon-nitrogen layer 20 by plasma enhanced chemical vapor deposition, wherein the thickness of the corrosion-resistant layer is 10 μm, wherein the thickness of the nano titanium nitride layer 31 is 6 μm, and the thickness of the nano titanium carbide layer 32 is 4 μm. The deposition temperature of the nano titanium nitride layer is 620°C, the deposition time is 5 hours, the obtained titanium nitride grain size is 350 nm, and the titanium nitride layer thickness is 5.5 μm; the deposition temperature of the nano titanium carbide layer is 610°C, the deposition time is 5 hours, the obtained titanium carbide grain size is 200 nm, and the titanium carbide layer thickness is 3.5 μm.
[0067] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.24; the volume wear rate is 3.2×10 -7 cm 3 / N·m.
[0068] Example 6
[0069] The difference from Example 5 is that when forming the carburizing-silicon-nitrogen layer 20, the temperature of the carburizing-silicon-nitrogen process is 350°C, the carburizing-silicon-nitrogen time is 2 hours, and the thickness is 110 μm.
[0070] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.26; the volume wear rate is 3.4×10 -6 cm 3 / N·m.
[0071] Example 7
[0072] The difference from Example 5 is that the nano titanium nitride layer 31 and the nano titanium carbide layer 32 are formed respectively by the low-temperature chemical deposition method in Example 1.
[0073] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.16; the volume wear rate is 2.8×10 -7 cm 3 / N·m.
[0074] Example 8
[0075] The difference from Example 5 is:
[0076] The thickness of the carburized-silicon-nitrogen layer 20 is 140 μm, the thickness of the nano-titanium nitride layer 31 is 3 μm, and the thickness of the nano-titanium carbide layer 32 is 4 μm.
[0077] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.23; the volume wear rate is 3.1×10 -7 cm 3 / N·m.
[0078] Example 9
[0079] The difference from Example 5 is:
[0080] The thickness of the carburized-silicon-nitrogen layer 20 is 160 μm, the thickness of the nano-titanium nitride layer 31 is 6 μm, and the thickness of the nano-titanium carbide layer 32 is 1 μm.
[0081] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.24; the volume wear rate is 3.3×10 -7 cm 3 / N·m.
[0082] Example 10
[0083] The difference from Example 5 is:
[0084] The thickness of the carburized-silicon-nitrogen layer 20 is 130 μm, the thickness of the nano-titanium nitride layer 31 is 2 μm, and the thickness of the nano-titanium carbide layer 32 is 6 μm.
[0085] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.26; the volume wear rate is 3.5×10 -6 cm 3 / N·m.
[0086] Embodiment 11
[0087] The difference from Example 5 is that the particle size of the nano-titanium nitride particles in the nano-titanium nitride layer 31 is 100 nm, and the particle size ratio of the nano-titanium carbide particles in the nano-titanium carbide layer 32 is 2:1.
[0088] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.3; the volume wear rate is 3.5×10 -7 cm 3 / N·m.
[0089] Example 12
[0090] The difference from Example 5 is that the particle size of the nano-titanium nitride particles in the nano-titanium nitride layer 31 is 300 nm, and the particle size ratio of the nano-titanium carbide particles in the nano-titanium carbide layer 32 is 1:6.
[0091] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.32; the volume wear rate is 3.7×10 -7 cm 3 / N·m.
[0092] Comparative Example 1
[0093] The difference from Example 5 is that a titanium nitride layer with titanium nitride particles having a particle size of 1 μm is used instead of the nano titanium nitride layer 31 .
[0094] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.35; the volume wear rate is 7.5×10-7 cm 3 / N·m.
[0095] Comparative Example 2
[0096] The difference from Example 5 is that a titanium carbide layer with a particle size of 1 μm is used instead of the nano titanium carbide layer 32 .
[0097] The friction coefficient of the corrosion-resistant layer on the surface of the drill pipe body 10 is 0.36; the volume wear rate is 7.1×10 -7 cm 3 / N·m.
[0098] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the composite structure layer formed by the above-mentioned carburized-silicon-nitrogen layer, nano-titanium nitride layer and nano-titanium carbide layer has excellent characteristics such as high hardness, strong bonding, low wear and high corrosion resistance, which can significantly improve the surface hardness of the drill pipe and reduce the wear rate of the drill pipe, thereby improving the wear resistance and corrosion resistance of the drill pipe.
[0099] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A drill pipe, characterized in that: The drill pipe comprises a drill pipe body (10), a carburized-silicon-nitrogen layer (20) sequentially arranged on the surface of the drill pipe body (10), a corrosion-resistant layer (30), and a female joint (40) and a male joint (50) connected to the drill pipe body (10), wherein the corrosion-resistant layer (30) comprises: a nano titanium nitride layer (31), the nano titanium nitride being arranged on a surface of the carburized-silicon-nitrogen layer (20) away from the drill pipe body (10); A nano titanium carbide layer (32) is provided on a surface of the nano titanium carbide layer (32) that is away from the carburized-silicon-nitrogen layer (20).
2. The drill pipe according to claim 1, characterized in that: The thickness of the carburized-silicon-nitrogen layer (20) is 100 to 200 μm, and the total thickness of the nano titanium nitride layer (31) and the nano titanium carbide layer (32) is 4 to 10 μm.
3. The drill pipe according to claim 2, characterized in that: The thickness of the nano titanium nitride layer (31) is 3 to 6 μm, and the thickness of the nano titanium carbide layer (32) is 1 to 4 μm.
4. The drill rod according to any one of claims 1 to 3, characterized in that The particle size of the nano titanium nitride particles in the nano titanium nitride layer (31) is 100-400 nm.
5. The drill pipe according to claim 4, characterized in that The nano-titanium carbide in the nano-titanium carbide layer (32) is in the form of block-shaped particles, and the particle size of the block-shaped nano-titanium carbide particles is 100-200 nm.
6. The drill pipe according to claim 5, characterized in that The ratio of the particle size of the nano-titanium nitride particles in the nano-titanium nitride layer (31) to the particle size of the nano-titanium carbide particles in the nano-titanium carbide layer (32) is 1:2 to 4:
1.
7. A method for preparing a drill pipe according to any one of claims 1 to 6, characterized in that: The preparation method of the drill pipe comprises: Carburizing-silicon-nitrogen treatment is performed on the inner and outer surfaces of the drill pipe body (10) to form a carburized-silicon-nitrogen layer (20); Performing a first chemical deposition on the surface of the carburized-silicon-nitrogen layer (20) to form a nano titanium nitride layer (31); and A second chemical deposition is performed on the surface of the nano titanium carbide layer (32) to form the nano titanium carbide layer (32) and obtain the drill rod.
8. The method for preparing a drill pipe according to claim 7, characterized in that: The temperature of the carburizing-silicon-nitrogen treatment is 400-550° C., and the carburizing-silicon-nitrogen treatment time is 2-6 hours.
9. The method for preparing a drill pipe according to claim 7 or 8, characterized in that: The temperature of the first chemical deposition is 450-650° C., and the processing time is 1-5 hours.
10. The method for preparing a drill pipe according to claim 7 or 8, characterized in that: The temperature of the second chemical deposition is 450-650° C., and the processing time is 1-5 hours.
Citation Information
Patent Citations
Titanium-nitrogen-carbon-aluminum- oxygen nano ceramic coating on low carbon steel surface and preparation method thereof
CN103496211A
Low friction coatings with improved abrasion and wear properties and methods of making
CN104870692A
Erosion-resistant composite aluminum alloy drill rod and manufacturing process thereof
CN112901086A
Hard layer composite coated drill
JP1993024219U
Hard film, metal mold and tool coated with the hard film
JP2014015636A
